Pelanggaran Prinsip Miranda Rule pada Proses Penyidikan Perkara Pidana di Indonesia (Tinjauan Kasus Pengamen Cipulir Jakarta Selatan 2013) - Anzil Rahmahdila; Arfi Exza Dheo Renova (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2024)
The criminal justice system in Indonesia is plagued by various types of crimes, including official indifference, abuse of authority by officers, and human rights violations related to people's civil rights. The rights of suspects, which are fundamental human rights and are ingrained in them, are often ignored in the Indonesian criminal justice system, to the detriment of suspects. The case that attracted attention was an incident that occurred in 2013 in Cipulir, South Jakarta, where several buskers were accused of committing the crime of murder. This case surfaced after reports that detained buskers were not given their basic rights during the investigation process, which could be linked to a violation of Miranda Rule principles. This research aims to find out how the Miranda Rule principles guarantee the rights of suspects in the criminal justice system in Indonesia. The method used in this research is a normative method, using the concept of a statutory approach. The purpose of the results of this research is to understand that the Miranda Principle or known as Miranda rights is what happens when someone gives a warning to someone who is in danger. Namely the right to obtain/contact legal advisors/advocates. If unable, then given the opportunity to provide legal advice/advocate. The right to obtain legal assistance has been included in Articles 54, 55 and 114 of the Criminal Procedure Code. If he is unable to do so, the suspect has the right to be provided with legal advice by the relevant official or through an investigator, as regulated in article 56 paragraph 1 of the Criminal Procedure Code. As for Miranda Warning (Right To Remain Silent), it is not regulated explicitly, but its application can be interpreted implicitly in articles 52, 117 and 166 of the Criminal Procedure Code.